2005
DOI: 10.1111/j.1365-2621.2005.tb09069.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Influences of Water Loss and Polyphenol Oxidase Activity on Anthocyanin Content and Discoloration in Fresh Ripe Strawberry (cv. Oso Grande) During Storage at 1 °C

Abstract: : Fresh‘Oso Grande’strawberries wrapped in polyvinyl chloride stretch film lost 0.7% of their initial weight during storage for 8 d at 1 °C, whereas unwrapped fruit lost 11%. Greater water loss was associated with darker and less red fruit, lower concentrations of anthocyanins and other soluble phenolics, and higher polyphenol oxidase (PPO) activity. Anthocyanin degradation and oxidation of soluble phenolic compounds, caused possibly by increased PPO activity as a result of water loss, contributed to the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 36 publications
3
57
1
Order By: Relevance
“…Decreases in L* value of strawberry fruits have previously been reported by others researches (Almenar et al, 2007;Harker et al, 2000). However, in our study, strawberry fruits stored at 4 °C tended to be brighter (higher L* value) This, according to Nunes et al, 2005, might be due to greater water loss and associated browning during storage at 20 °C. The a* value increased significantly in fruits stored at 4 °C, This response could be related to the accumulation of anthocyanin pigments and high degree of red fruits.…”
Section: Fruit Quality Experimentscontrasting
confidence: 55%
See 1 more Smart Citation
“…Decreases in L* value of strawberry fruits have previously been reported by others researches (Almenar et al, 2007;Harker et al, 2000). However, in our study, strawberry fruits stored at 4 °C tended to be brighter (higher L* value) This, according to Nunes et al, 2005, might be due to greater water loss and associated browning during storage at 20 °C. The a* value increased significantly in fruits stored at 4 °C, This response could be related to the accumulation of anthocyanin pigments and high degree of red fruits.…”
Section: Fruit Quality Experimentscontrasting
confidence: 55%
“…Data for firmness showed a significant effect of the interaction G × S (Tables 2 and 4) with the highest figure in the combination 'Candonga Sabrosa' either with fruit storage at 4 °C or at 20 °C and the lowest in the combination 'Sant Andreas' × fruit storage at 20 °C. It is known that the mechanical properties of fruits are related to firmness and, depend on cell wall strength, cell-to-cell adhesion, cell packing and the internal pressure or turgor of cells (Nunes et al, 2005). Softening of strawberry fruits during storage is mainly due to loss of cell wall material, which is more pronounced in the cortical tissue than in the pith tissue (Koh et al, 1997).…”
Section: Fruit Quality Experimentsmentioning
confidence: 99%
“…The pericarp's temperature was lower than the ambient temperature because of litchi's transpiration. It meant that litchi coated with chitosan Chitosan Edible Coating have been found to be more marked in ripe strawberries that suffer greater moisture loss during storage (Nunes et al, 2005). The control of moisture loss by chitosan coatings contributes to minimizing external colour changes in fully ripe strawberries.…”
Section: Respiration Ratementioning
confidence: 99%
“…It is thus to be expected that colour differences between control and coated strawberries be more accentuated in fruit stored at higher temperatures. It is also reported that factors that could also have an influence on the development of dark-colored pigments include changes in ascorbic acid and in sugar profiles, peroxidase activity, and other phenolic compounds that are good substrates for enzymatic browning (Nunes et al, 2005).…”
Section: Respiration Ratementioning
confidence: 99%
“…Water loss accelerates senescence of the fruit and the maximum permissible amount of water that can be lost (based on weight loss) from the fruit before becoming unmarketable is 6%. During postharvest handling of the berries, water loss can be reduced by prompt precooling and adequate packaging and storage at optimum temperature and relative humidity [24].…”
Section: Storagementioning
confidence: 99%